Sacagawea : journey into the west - Gunderson, Jessica (Graphic library : graphic biographies, 2007)
Tells the story of Sacagawea, the teenage Shoshone mother who traveled with the Lewis and Clark expedition as an interpreter. Written in graphic-novel format.